1997
DOI: 10.1136/gut.41.6.785
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell mediated ion transport in intestine from patients with and without inflammatory bowel disease

Abstract: Background-Mast cells have been shown to regulate intestinal ion transport in animal models and normal human colon but their physiological role in human intestinal inflammatory disorders is unknown. Aims-To examine mast cell regulation of ion transport in inflammatory bowel disease (IBD). Subjects and methods-Small and large intestine was obtained from patients with and without IBD undergoing surgical resection. Short circuit current (Isc) responses to rabbit antihuman IgE, histamine, and electrical stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 34 publications
(29 reference statements)
2
60
0
Order By: Relevance
“…Similar diminished Isc responsiveness has been observed in other animal models of colitis and in tissue resections from patients with inflammatory bowel disease. [31][32][33][34] However, neither ROL nor PTX treatment led to any amelioration of the reduced Isc responses, clearly indicating uncoupling of structure and function in this model of colitis. Juxtaposition of these data with the histological portion of the study suggests that either regulation of Isc is more readily altered than derangement of colon structure, or that ion transport and colon structure are regulated by different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Similar diminished Isc responsiveness has been observed in other animal models of colitis and in tissue resections from patients with inflammatory bowel disease. [31][32][33][34] However, neither ROL nor PTX treatment led to any amelioration of the reduced Isc responses, clearly indicating uncoupling of structure and function in this model of colitis. Juxtaposition of these data with the histological portion of the study suggests that either regulation of Isc is more readily altered than derangement of colon structure, or that ion transport and colon structure are regulated by different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In sensitized mast cell-deficient mice, secretory response to serosal antigen was reduced by 70% in comparison to normal congenic mice, but fully restored after reconstitution of intestinal mast cell population by injecting bone marrow-derived mast cell precursors. 11,59 Others demonstrated that the compound 48/80-induced and anti-IgE-induced secretory response could be reduced by ketotifen and H 1 R antagonist in chicken ileum 60 and human colon, 57 respectively. Furthermore, SP stimulated net ion secretion could be reduced partly by H 1 R and H 2 R antagonists and a mast cell stabilizer (doxantrazole).…”
Section: Mast Cells Regulate Epithelial Secretionmentioning
confidence: 99%
“…55,56 In vitro studies have clearly demonstrated that MC activation alters intestinal epithelial ion transport directly or indirectly (via intrinsic or extrinsic nerves), 57,58 through recording the transepithelial short-circuit current of the intestinal mucosal tissues or epithelial cell monolayers. In sensitized mast cell-deficient mice, secretory response to serosal antigen was reduced by 70% in comparison to normal congenic mice, but fully restored after reconstitution of intestinal mast cell population by injecting bone marrow-derived mast cell precursors.…”
Section: Mast Cells Regulate Epithelial Secretionmentioning
confidence: 99%
“…Mast cells have been shown by a number of groups to modify the epithelial barrier function within the intestine and, when activated, to increase intestinal permeability and fluid loss. [53][54][55][56][57] Such processes could explain enhanced weight loss in mast cell-containing animals.…”
Section: Discussionmentioning
confidence: 99%